MAKNA KATA BERDAMAI DALAM FRASA “BERDAMAI DENGAN COVID” DI ERA NEW NORMAL - Mustikasari, Rizki; Wlandari, Rifa Suci; Harida, Ratri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Meaning is the liaison of language with the outside world agreed by the speakers so that they can understand each other. On May 7, 2020 through the President's Presidential Secretariat YouTube channel, President Joko Widodo gave a speech on the implementation of the PSBB. In the speech, the President said "berdamai dengan COVID". The phrase becomes polemic in the community. Some people consider the word “berdamai” is not suitable to use to deal with COVID. Some other groups say that the word “berdamai” in the phrase "berdamai dengan COVID" is the correct use. This paper discusses the meaning of the word "berdamai" in the phrase "berdamai dengan COVID". Determination of meaning is based on the context of the phrase "Berdamai dengan COVID" or contextual meaning. Based on the context of the situation, the word “berdamai” in the phrase "berdamai dengan COVID" does not mean mutually agreeing, or stopping to attack each other as found in the KBBI. Rather it means trying to adjust to new circumstances so that you can feel peace.